Quantificação da incerteza de sistemas vibratórios discretos via método de Faedo-Galerkin-Estocástico - Cavichiolo, Joao Lucas (2020)
The quantification of uncertainties is a procedure more and more common at computacional simulations especially for problems that involve dynamics and vibration. Several methods, probabilistic or not, of uncertainties qualification has been used in such simulations. The Monte Carlo method is the most used because your simplicity, however your slow convergence and high computational cost are more evident in large scale problems. Other methods like Galerkin method has been widely used in the uncertainties qualification due your better efficiency than others methods. This work will present quantification uncertainties applied at discrete dynamic systems using Stochastic Faedo-Galerkin method, were the uncertainties will be included in material parameters. The obtained results are compared to obtained results by Monte Carlo simulation.